Analysis of Flood Hazards and Risk in the Sirimau District Ambon City - Mohammad Amin Lasaiba (Universitas Negeri Semarang, 2023)
This study aims to target the threat and risk of flooding in Sirimau District, Ambon City from a multi-criteria perspective using a Geographic Information System (GIS). Important flood hazard characteristics include land use, elevation, slope, distance from rivers, soil, and rainfall. Two risk factors, namely population density and land use as well as flood hazard characteristics are used in flood risk analysis. Map aggregation procedure for flood risk and hazard analysis uses the Weighted Linear Combination (WLC) approach. The results of the flood hazard at the study site revealed that the flood hazard category was very high and high, namely 12.26%, and the flood hazard category was very low and low, namely 87.84% and only. The results of the flood risk in the research location revealed that the flood risk with very high and high-risk categories was around 17.28%, and very low and flood low-risk categories (82.77%). This is because the Sirimau District is mostly dominated by hilly and mountainous areas.